2020
DOI: 10.1038/s41534-020-00312-y
|View full text |Cite
|
Sign up to set email alerts
|

Giant shift upon strain on the fluorescence spectrum of VNNB color centers in h-BN

Abstract: We study the effect of strain on the physical properties of the nitrogen antisite-vacancy pair in hexagonal boron nitride (h-BN), a color center that may be employed as a quantum bit in a two-dimensional material. With group theory and ab initio analysis we show that strong electron–phonon coupling plays a key role in the optical activation of this color center. We find a giant shift on the zero-phonon-line (ZPL) emission of the nitrogen antisite-vacancy pair defect upon applying strain that is typical of h-BN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 56 publications
(83 reference statements)
6
33
0
Order By: Relevance
“…Hence, including the effect of substrate surface on the SPEs demands further investigations, which remains an open subject for future studies. We note here that recent calculations on color centers in hexagonal boron nitride have demonstrated that the number of boron nitride layers has minimal effect on the ZPL of the color centers [36]. Similarly, we expect that 2D-SiC monolayers form weak bonds with the substrate, and thus only cause slight modification in the properties of the localized defect states.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Hence, including the effect of substrate surface on the SPEs demands further investigations, which remains an open subject for future studies. We note here that recent calculations on color centers in hexagonal boron nitride have demonstrated that the number of boron nitride layers has minimal effect on the ZPL of the color centers [36]. Similarly, we expect that 2D-SiC monolayers form weak bonds with the substrate, and thus only cause slight modification in the properties of the localized defect states.…”
Section: Resultssupporting
confidence: 49%
“…Another critical effect which lies at the heart of our analysis is the electric dipole interaction that determines dark and bright states. Those states that their dipole moment can couple to the ground state via the external electric field, provided by electromagnetic radiation, determine the selection rules [35,36]. In this part of study, the value of matrix elements ψ|O|φ is vanishing if their total irreducible symmetry is not that of totally symmetric irreducible representation, here A 1 and A for the C 2v and C s , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The ab initio analysis provided in the previous section has allowed us to find the effect of local strain on the energy levels of negatively charged boron vacancy defects (V B ). Our results suggest that the deformation potential for the simulated configuration (a monolayer hBN) becomes as large as Ξ = 2.98 PHz/strain for stretch or compression along the armchair direction, which is in the same order of magnitude that has been previously reported by some of us for the complex antisite defect (V N N B ) in hBN [12]. Such large deformation susceptibility emerges thanks to the two-dimensional nature of the setup and has the potential of leading us to the strong interaction between the vibrational modes and the color centers.…”
Section: B Hamiltonian Of the Systemsupporting
confidence: 85%
“…In the later experiments larger effect of the strain was further revealed by modifying the setup [10,11]. On the theory side, the computational analysis on the effect of strain on the antisite complex defects V N N B , that are counted as one of the main candidates of quantum emission from hBN, proved that the sensitivity of these color centers to the local strain is significant [12]. Meanwhile, there are other point defects responsible for the single-photon emission such as boron vacancy that has shown interesting electronic and magnetic properties such as optical polarization of their ground state [13,14].…”
Section: Introductionmentioning
confidence: 97%
“…Technical overhead could be further reduced when the need for cryogenics is eliminated which requires detailed studies of electron-phonon interaction [18][19][20]. Defect centers in hBN show, for example, almost unity quantum efficiency [21], giant strain-induced shift of the zero-phonon-line (ZPL) emission [22] and, in particular, Fourier transform-limited (FTL) optical transitions under resonant excitation at cryogenic temperatures [23] as well as room temperature (RT) [24]. Remaining limitations, for example originating from on-going spectral diffusion and thermally generated phonon interactions under off-resonant excitation are currently investigated and continuously improved [25].…”
Section: Introductionmentioning
confidence: 99%